The Potential of Farmer Field School in Cocoa Extension Delivery:A Ghanaian Case Study - Ernest L. Okorley; Gabriel Adjaro; Martin Bosompem (Journal of International Agricultural and Extension Education, 2014)
The potential of Farmer Field School (FFS) as an extension approach in Africa is still evolving, with limited empirical evidence. Cocoa FFSs have been introduced in Ghana by the Ministry of Food and Agriculture and Ghana Cocoa Board (COCOBOD) since 2006, and are still being experimented with by COCOBOD and NGOs. But, little is known about its effects on farmers to inform COCOBOD’s quest to mainstream and support it. This study, therefore, ascertains the potential of the FFS in terms of its effectiveness and impact on livelihoods of cocoa farmers in Ghana. Using a retrospective comparison design, a survey was conducted on beneficiaries of cocoa FFS in the Mpohor Wassa East District of the Western Region of Ghana. The case study found that the FFS was effective in facilitating farmers' acquisition of knowledge in all cocoa technologies practiced under the FFS. The participant farmers perceived their yields to have increased significantly up to 79%, and their household livelihoods improved due to the FFS. It was also perceived to have improved all capital assets of the farmers, with human capital being the most affected. The best predictors of impact on the livelihoods of the cocoa farmers in FFS were mirid control practices (40.7%), followed by training and extension methods (7.4%). It can be concluded from this case study that FFS can be an effective tool for cocoa extension in Ghana based on the confidence the study farmers have shown regarding its ability to improve farmer competence, yields, and household livelihoods
Keywords: Extension; Cocoa; Farmer Field School; Impact; Livelihoods; Ghana